2014
DOI: 10.1371/journal.pone.0099325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Processing and Maceration on the Antioxidant Activity of White Beans

Abstract: Phenolic compounds, which naturally occur in beans, are known to have antioxidant activity, which may be partially lost during the processing of this legume. This study evaluated the effect of thermal processing and maceration on the phenolic acid and flavonoids profile and content and on the antioxidant activity of white beans. According to the results obtained from the 2,2-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) method, there were no significant differences among treatment g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
(67 reference statements)
2
11
0
2
Order By: Relevance
“…For cooked and soaked beans, no differences were found between the fractions, except for fraction 3, which presented the lowest antioxidant activity amongst the samples. As in the present study, Huber et al (2014) reported a large variation between the results obtained for antioxidant activity, depending on the composition of the fraction analysed.…”
Section: Fractionssupporting
confidence: 58%
See 4 more Smart Citations
“…For cooked and soaked beans, no differences were found between the fractions, except for fraction 3, which presented the lowest antioxidant activity amongst the samples. As in the present study, Huber et al (2014) reported a large variation between the results obtained for antioxidant activity, depending on the composition of the fraction analysed.…”
Section: Fractionssupporting
confidence: 58%
“…Cooking had no effect on fractions 2 and 4 of Phenolic compounds and antioxidant activity of two bean cultivars (Phaseolus vulgaris L.) submitted to cooking Silva, M. O. et al the commercial bean and on the fraction 4 of the Pontal bean. Huber et al (2014) also reported a reduction in the antioxidant activity of certain fractions after cooking when using the ABTS method, with fraction 4 exhibiting the highest antioxidant activity for cooked white beans without soaking.…”
Section: Fractionsmentioning
confidence: 92%
See 3 more Smart Citations